PCA-Assisted Raman Analysis of Osteonecrotic Human Femoral Heads - Eiji Ishimura; Wenliang Zhu; Elia Marin; Taigi Honma; Nobuhiko Sugano; Wataru Ando; Giuseppe Pezzotti (Methods and Protocols, 2022)
Osteonecrosis of the femoral head (ONFH) occurs frequently in adolescents and young adults and causes progressive deformation and destruction of the hip joint and impairs standing and walking, resulting in a significant decrease in the quality of life of patients. In addition, studies have shown that a history of corticosteroid administration and heavy alcohol consumption are closely related to the occurrence of ONFH. However, the detailed mechanism by which steroid administration and alcohol consumption are associated with the development of the disease is still unknown. With many researches still ongoing and without a clear biological pathway for osteonecrosis, effective preventive measures cannot be taken. Therefore, the current focus of ONFH treatment is to establish an early diagnosis and treatment strategy. We obtained the femoral heads of four patients with steroidal ONFH and three patients with alcoholic ONFH. We then compared the femoral heads of steroidal and alcoholic osteonecrosis by analyzing them at the molecular level by Raman spectroscopy. Crystallographic changes (deformations) in the mineral phase and fraction of organic material respect to the total mass were then plotted as a function. We found that changes in bone composition in ONFH were different in steroidal and alcoholic ONFH. We conclude that this suggests that the developmental mechanisms of steroidal and alcoholic ONFH may follow different paths. We also noticed that while steroid seem to lead to a more marked degradation of the tissue, alcohol seem to affect also the quality of the healthy tissue.